2015
DOI: 10.1093/annonc/mdu253
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of colorectal cancer in older patients: International Society of Geriatric Oncology (SIOG) consensus recommendations 2013

Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed cancers in Europe and worldwide, with the peak incidence in patients >70 years of age. However, as the treatment algorithms for the treatment of patients with CRC become ever more complex, it is clear that a significant percentage of older CRC patients (>70 years) are being less than optimally treated. This document provides a summary of an International Society of Geriatric Oncology (SIOG) task force meeting convened in Paris in 2013 to update the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
258
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(279 citation statements)
references
References 132 publications
3
258
1
2
Order By: Relevance
“…Colorectal carcinoma (CRC) is a common type of cancer in developed and developing countries (1). CRC is refractory to current therapeutic strategies, due to the lack of knowledge regarding the molecular mechanisms underlying CRC (2).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal carcinoma (CRC) is a common type of cancer in developed and developing countries (1). CRC is refractory to current therapeutic strategies, due to the lack of knowledge regarding the molecular mechanisms underlying CRC (2).…”
Section: Introductionmentioning
confidence: 99%
“…Screening tools available can be incorporated into the preoperative evaluation of the surgical practice to mitigate complications. Although assessment tools are clearly not an alternative to sound clinical judgment of the surgeon, or honest communication with the patient, there is a growing body of evidence supporting the necessity to use objective scores [9,10]. However, thus far it has been shown that the use of screening tools has not been widely adopted by surgeons [29].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is understood that the older population should not be assessed on chronologic age, but rather frailty, functionality, and dependency [7,8]. The International Society of Geriatric Oncology (SIOG) task force has recommended a Comprehensive Geriatric Assessment (CGA) along with several other screening tools for evaluating an elderly patient for surgery [9,10]. These evaluations have been shown to be predictive of adverse outcomes after an oncological operation in an elderly patient.…”
Section: Screening Toolsmentioning
confidence: 99%
“…Currently, patients with stage I or II colorectal cancer are treated with surgery, while patients with stage III colorectal cancer are treated with surgery followed by adjuvant chemotherapy, and patients with metastatic colorectal cancer (mCRC) are treated with systemic chemotherapies alone or in combination with targeted biologics [3][4]. However, most of the colon cancer patients develop resistance to adjuvant chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%